(untitled) (Scientific journal of the Fergana State University, 2024)
This article deals with the introduction of the Zingiber officinale L. plant in the soil and climatic conditions of Termiz district and the distribution areas and botanical description of the plant, the seasonal development pattern. Ginger (Zingiber officinale L.) is a spice and medicinal plant belonging to the ginger family.